New leash on life [large type] - Y'Barbo, Kathleen (Gone to the dogs mysteries, 2023)
"Air Force veteran Dr. Lane Bishop and Nora Hernandez's romance has cooled. He is busy working as a researcher at the vet school, and she's busy with her restaurant and opening an antique shop. What Lane hasn't told her is that his PTSD, which manifests mostly with nightmares, makes him believe he's damaged goods. But that is about to change when he meets a stray pup that acts a lot like a military working dog. When a tornado hits Brenham, there is damage in the downtown area and a fire is ignited in Nora's new store. A Belgian Malinois dog is seen at the fire and later Lane sees him at a wedding venue where an explosion occurs. Not long after, a second explosion rocks Brenham and sends Nora and Lane on a hunt for the person responsible. Will the pair find the guilty party before more damage is done to the city's landmarks? And will Lane find the words to tell Nora how much he loves her before it's too late?"--